Effect of irradiation by 140 Mev Ag11+ ions on the optical and electrical properties of polypropylene/TiO2 composite - GÜLLÜOĞLU, ARİF NİHAT (ELSEVIER, 2009)
Changes in the optical, structural, dielectric properties and surface morphology of a polypropylene/TiO2 composite due to swift heavy ion irradiation were studied by means of UV-visible spectroscopy, X-ray diffraction, impedance gain phase analyzer and atomic force microscopy. Samples were irradiated with 140 MeV Ag11+ ions at fluences of 1 x 10(11) and 5 x 10(12) ions/cm(2). UV-visible absorption analysis reveals a decrease in optical direct band gap from 2.62 to 2.42 eV after a fluence of 5 x 10(12) ions/cm(2). X-ray diffractograms show an increase in crystallinity of the composite due to irradiation. The dielectric constants obey the Universal law given by epsilon proportional to integral(n-1), where n varies from 0.38 to 0.91. The dielectric constant and loss are observed to change significantly due to irradiation. Cole-cole diagrams have shown the frequency dependence of the complex impedance at different fluences. The average surface roughness of the composite decreases upon irradiation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Polypropylene/TiO2 composite; Electrical measurement; Optical spectroscopy; X-ray diffraction; Atomic force microscope; FILMS; TIO2; GAP